Parental attitudes towards dental aesthetics and treatment needs in children: a questionnaire study - Bhatt, Garima; Sodani, Vasudha; Iyer, Sowjanya; Shah, Harsh; Dhruv, Keyur (International Journal Of Community Medicine And Public Health, 2025)
Background: Dental aesthetics play a crucial role in child’s psychological and social development. Parents play a pivotal role in decision making and thus understanding their attitudes can help dental professionals provide tailored interventions to improve pediatric dental health. Thus, the present study was conducted with the aim to assess parental attitudes, perceptions and concerns regarding dental aesthetics and treatment needs of their children and to evaluate the factors influencing their decisions in seeking dental care. Methods: This cross sectional study utilizes a structured and validated Google questionnaire form that aims to elicit responses regarding parental attitudes, perceptions and concerns about dental aesthetics and treatment needs. After the sample size determination, forms were circulated among parents and a total of 981 responses were obtained which were analyzed statistically. Results: Among the total of 981 parents, 886 parents (90.5%) strongly believed that tooth color affects their child’s confidence, 500 parents (51.1%) expressed concerns regarding the structure of teeth. Majority of parents (877, 89.5%) considered all the factors (aesthetic, durability, cost) in choosing the type of restoration. Results depicted a strong preference for aesthetic treatments with majority of the parents (795, 81.2%) choosing tooth colored restorations, thereby revealing paradigm shift towards aesthetic treatments in pediatric dentistry. Conclusions: This study highlights growing parental awareness and concern regarding dental aesthetics in children, with an increasing preference for aesthetic solutions. This evolving trend presents a valuable opportunity for clinicians to offer broad spectrum of aesthetic treatment options tailored to individual needs, thereby elevating clinical practice.